Disparity Indices and Overweight: Frame of Reference - Wendell C. Taylor; Casey P. Durand; Gregory Knell (Mary Ann Liebert, 2019)
Purpose: The purpose of this study was to compare state rankings of body mass index (BMI) among three different indices of income disparities (i.e., low-, middle-, and high-income thresholds) and BMI. One measure of disparities was based on national standards and the other measure was based on state-specific data. Methods: Data were from the 2016 Behavioral Risk Factor Surveillance System and analyzed in 2018. To assess differences between the two indices, Spearman Rank Order Correlation coefficient with a Bonferroni adjustment and kappa statistic were used. Results: Spearman rank-order correlation coefficient with a Bonferroni adjustment found that the two indices had a very weak monotonic relationship (?=0.11, p=0.46). The kappa value [? (df=48)=0.02, p-value=0.43] revealed the indices were not concordant. The rankings of states based on national and state-specific disparity indices were distinctly different. Conclusion: Our study highlights the importance of choosing disparity indices. To analyze state similarities and differences, findings and interpretations are different when using a national standard applied to all states versus state-specific data as the frame of reference for the disparity index. Future research is needed to confirm the generalizability of our findings. In addition to income, our approach can be used with other sociodemographic variables such as age, race/ethnicity, sex, and education. The overall goal is to present a comprehensive and nuanced perspective of disparities contributing to the overweight/obesity epidemic.